2022
DOI: 10.1136/bmjopen-2021-052752
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody prevalence and correlates of six ethnic groups living in Amsterdam, the Netherlands: a population-based cross-sectional study, June–October 2020

Abstract: ObjectivesIt has been suggested that ethnic minorities have been disproportionally affected by the COVID-19. We aimed to determine whether prevalence and correlates of past SARS-CoV-2 exposure varied between six ethnic groups in Amsterdam, the Netherlands.Design, setting, participantsParticipants aged 25–79 years enrolled in the Healthy Life in an Urban Setting population-based prospective cohort (n=16 889) were randomly selected within ethnic groups and invited to participate in a cross-sectional COVID-19 ser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…During the same year, higher seropositivity rates were observed in New York City (May–July 2020; 18+ years; 23.6% [ 10 ] and June–October 2020; 18+ years; 24.3% [ 11 ]), Saudi-Arabia (May–July 2020; 18+ years; 19.3%) [ 12 ], Ireland (June–July 2020; 18+ years; 12.6%) [ 13 ], and Mexico (August–November 2020; 20–39 (27.9%), 40–59 (27.8%) and 60+ (18.6%) years) [ 14 ]. Similar rates were observed in Ethiopia (June–July 2020; 15+ years, 3.2%) [ 15 ], England (April–September 2020; 18–65 years; 5.9%) [ 16 ], Amsterdam, the Netherlands (June and October 2020; 18–70 years, 9.4%) [ 17 ], Germany (May–June 2020; 18+ years; 11.3%) [ 10 ], and the United States (July 2020 (3.5%), December 2020 (11.5%); 16+ years) [ 18 ]. In Australia, between April and June 2020, the seropositivity rate among 20 year olds and above was lower than 1% [ 19 ].…”
Section: Discussionsupporting
confidence: 69%
“…During the same year, higher seropositivity rates were observed in New York City (May–July 2020; 18+ years; 23.6% [ 10 ] and June–October 2020; 18+ years; 24.3% [ 11 ]), Saudi-Arabia (May–July 2020; 18+ years; 19.3%) [ 12 ], Ireland (June–July 2020; 18+ years; 12.6%) [ 13 ], and Mexico (August–November 2020; 20–39 (27.9%), 40–59 (27.8%) and 60+ (18.6%) years) [ 14 ]. Similar rates were observed in Ethiopia (June–July 2020; 15+ years, 3.2%) [ 15 ], England (April–September 2020; 18–65 years; 5.9%) [ 16 ], Amsterdam, the Netherlands (June and October 2020; 18–70 years, 9.4%) [ 17 ], Germany (May–June 2020; 18+ years; 11.3%) [ 10 ], and the United States (July 2020 (3.5%), December 2020 (11.5%); 16+ years) [ 18 ]. In Australia, between April and June 2020, the seropositivity rate among 20 year olds and above was lower than 1% [ 19 ].…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, we found strong associations with being born outside the Netherlands and not using the app. If national app usage trends reflect those found in our sample, this would be worrisome given that previous studies in Amsterdam and internationally have shown that some ethnic minority groups are disproportionately affected by SARS-CoV-2 [31][32][33][34][35][36]. Cultural differences or distrust in the authorities may underlie this observation, but other more practical issues might be important as well.…”
Section: Comparison With Prior Workmentioning
confidence: 53%
“…Unfortunately, the routine data used in this study do not contain information on language skills or parental birth country, and thus we cannot investigate app use among second-generation immigrants. Further research in this group is therefore needed to reduce health inequalities between ethnic groups [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies in Africa with lower specificity of IgG and IgM to predicting COVID-19 diagnosis. These results may be related to the intensity of immune response between different races to produce antibodies against the SARS-CoV-2 infection ( 35 , 36 ). Previous study has shown that Hispanics and Blacks had higher rates of SARS-CoV-2 antibodies than Whites, indicating that SARS-CoV-2 spread disproportionately in racial and ethnic minorities during the COVID-19 pandemic ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%